(untitled) (Revista Cocar, 2015)
Esta é a primeira edição especial da Revista Cocar, cujo dossiê "Educação Especial na perspectiva da Educação Inclusiva" foi aprovado em edital da Associação Nacional de Pós-Graduação e Pesquisa em Educação - ANPED e financiado pela Fundação de Apoio à Pesquisa da Universidade Federal de Goiás - FUNAPE. O tema foi proposto por se considerar de grande importância para a educação brasileira, uma vez que a educação especial na perspectiva inclusiva considera o direito de todos/as à educação pública e de qualidade social, entre os quais estudantes com deficiência, transtornos globais de desenvolvimento e altas habilidades. Editorial This is the first special edition of the Revista Cocar, whose dossier "Special Education in the perspective of Inclusive Education" was approved by the National Association of Graduate Studies and Research in Education - ANPED and funded by the Research Support Foundation of the Federal University of Goiás - FUNAPE. The theme was proposed as being of great importance for Brazilian education, since special education in an inclusive perspective considers the right of all to public education and social quality, among which students with disabilities, global development disorders And high skills.